2014
DOI: 10.1007/s00246-014-1039-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-Pericardiotomy Syndrome in Pediatric Patients Following Surgical Closure of Secundum Atrial Septal Defects: Incidence and Risk Factors

Abstract: Surgical repair for atrial septal defects (ASD) generally occurs during childhood. Post-pericardiotomy syndrome (PPS) after cardiac surgery has a reported incidence of 1-40 %. We focused exclusively on secundum ASD repair to evaluate the incidence of PPS. The purpose of this study is to determine the incidence of PPS after surgical repair of secundum ASD and investigate what risk factors may be predictive of its development. A retrospective study was performed, and 97 patients who underwent surgical closure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 20 publications
3
23
1
Order By: Relevance
“…Postpericardiotomy syndrome is a common complication of cardiac surgery, with an incidence of between 3% and 28% depending on the diagnostic criteria used. 1417 As demonstrated in this study, PPS does not only incur economic cost but also can cause morbidity and, tragically, mortality. It thus should be considered in analyses comparing outcome after operative and transcatheter ASD closures.…”
Section: Discussionmentioning
confidence: 76%
“…Postpericardiotomy syndrome is a common complication of cardiac surgery, with an incidence of between 3% and 28% depending on the diagnostic criteria used. 1417 As demonstrated in this study, PPS does not only incur economic cost but also can cause morbidity and, tragically, mortality. It thus should be considered in analyses comparing outcome after operative and transcatheter ASD closures.…”
Section: Discussionmentioning
confidence: 76%
“…Treatment options are fluid restriction, diuretic use, corticosteroid therapy, non-steroidal anti-inflammatory drugs, and, in case of cardiac tamponade, (surgical) pericardial drainage [35]. Compared to other pediatric studies investigating PE [7, 8, 1315, 36], treatment of patients with crPE in this study was mainly conservative or with diuretics, with corticosteroids prescribed for more severe cases. Yet, corticosteroids did not seem to influence the progression of crPE, since patients with and without corticosteroids still required pericardial drainage just as often (22.8% vs. 25.7%, p  = 0.71).…”
Section: Discussionmentioning
confidence: 99%
“…In the major PPS studies during the last decades, the reported incidences have been the following: 10-28% in children [32][33][34][35][36] and 9-21% in adults [8,12,13,37,38] with a median of 16% in adult patients [14]. In the recent Colchicine for Prevention of Postpericardiotomy Syndrome and Postoperative Atrial Fibrillation (COPPS-2) trial [7], the incidence in adult patients was as high as 29% in elderly patients, although the time limit of fever was abandoned resulting in a markedly higher occurrence during the first postoperative days compared to the Colchicine for the Prevention of the Post-pericardiotomy Syndrome (COPPS) trial [8].…”
Section: Epidemiology Of Ppsmentioning
confidence: 99%
“…PPS typically occurs within one month after the surgery, and an initial onset after six months is rare [5,12,13,26,[43][44][45][46][47]. In children, the onset is slightly earlier, typically within 1 to 2 weeks [11,33,35]. The median duration of the syndrome is 2-3 weeks [28,35,46], and possible relapses tend to occur within 2-11 weeks after the initial onset [44].…”
Section: Clinical Features Of Ppsmentioning
confidence: 99%